Teacher preparedness and student outcomes: A study on the effectiveness of special education instructional practices - Alnajar, Ayesha Abdulrahman; Alnoaim, Jehad; Alhossyan, Fawaz; Etiwa, Mohamed Alhosany (International Journal of Innovative Research and Scientific Studies, 2025)
Behind every successful student is a well-prepared teacher. This quantitative study investigates how Saudi preservice special education teachers perceive their preparedness in relation to their peers regarding teaching students with disabilities in inclusive classrooms. The research analyzed three dimensions: overall perceived readiness, gender differences, and differences based on specialization (mild intellectual disability, learning disabilities, and hearing impairment). An instrument comprising 29 items was distributed to a sample of final-year preservice special education teachers. The data were analyzed statistically using SPSS, employing descriptive statistics, t-tests, and one-way ANOVA. The findings revealed a high overall perceived readiness (M = 3.21), particularly in areas such as classroom management, differentiated instruction, collaboration with general educators, and awareness of evidence-based practices (EBPs). However, the respondents rated their practical skills, such as developing Individualized Education Programs (IEPs) and actively implementing EBPs, relatively low, indicating notable gaps in their training. Additionally, no statistically significant differences were found based on gender (p = 0.455) or faculty track (p = 0.342), suggesting that students perceive a similar level of preparedness regardless of demographic factors. These findings imply that current training programs provide a foundational understanding of inclusive pedagogical management, demonstrating some effectiveness. Nonetheless, they emphasize the need for enhanced practical training, particularly in tailoring educational strategies to meet the diverse needs of students.